1983
DOI: 10.1192/bjp.142.6.621
|View full text |Cite
|
Sign up to set email alerts
|

The Causality of Depression in Schizophrenia

Abstract: The phenomenon of post-treatment depression in schizophrenia has become the subject of considerable controversy regarding its causality (Ananth and Chadirian, 1980; McGlashan and Carpenter, 1976a). But as the recent commentary by Hirsch (1982) emphasizes, the most controversial issue is focused on whether this depression is neuroleptic-induced. Hirsch himself refutes neuroleptic-induction on the basis of various uncontrolled data which seem ostensibly incompatible with this causality. Results indicating that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 14 publications
0
20
0
5
Order By: Relevance
“…thioridazine, may have antidepressive effects (32); on the other, neuroleptics have been accused of causing depression (33). There is no doubt that the issue of pharmacogenic neuroleptic-induced depression currently remains controversial (34). Neuroleptics, nevertheless, cannot be considered to be highly satisfactory antidepressants and certainly not the medication of choice in the treatment of depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…thioridazine, may have antidepressive effects (32); on the other, neuroleptics have been accused of causing depression (33). There is no doubt that the issue of pharmacogenic neuroleptic-induced depression currently remains controversial (34). Neuroleptics, nevertheless, cannot be considered to be highly satisfactory antidepressants and certainly not the medication of choice in the treatment of depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dopamine blockade by a neuroleptic drug could theoretically lead to anhedonia and, perhaps, depression. Indeed, a state of dysphoria is commonly described by neuroleptic-treated patients (34), a number of older anecdotal reports have suggested a link between neuroleptic use and depression (35)(36)(37)(38)(39), and one study found more anhedonia and depression in maintenance-phase schizophrenic patients who were taking neuroleptics than in others who were not (33). Another study found a positive relationship between haloperidol plasma levels and depressive symptoms in the context of a positive association between extrapyramidal symptoms and depressive symptoms (40), and impairments of quality of life related to neuroleptic-induced dysphoria have been reported (41).…”
Section: Neuroleptic-induced Dysphoriamentioning
confidence: 99%
“…According to Galdi, (14) depressive symptoms are due to the neuroleptic medication. The finding in my study are opposite to that.…”
Section: Group-b N=28 Totalmentioning
confidence: 99%